Determination of the physico-mechanical properties of three cultivars of Cowpea (Vigna unguiculata) grain - Adanu, E. O.; Iya, S. A.; Yakubu, I. T.; Kabri, H. U. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
This study evaluated the physico-mechanical properties of IT89KD-288, Ife brown, and IT98K-573-1-1 varieties of cowpea. The cowpeas were obtained from local farmers in different parts of North Eastern Nigeria. The crop varieties were identified, sundried and cleaned before testing. The results for length, width, thickness, equivalent diameter, arithmetic diameter, sphericity, surface area, volume, mass, angle of repose, frictional angle, and bulk density were obtained at pre-determined moisture contents. Other results for IT98K-573-1-1 seed-chaff ratio, pod angle of internal friction, hardness, compressive force in the major, intermediate and minor axes, shear force in the major, intermediate and minor axes are 4.0±0.18, 44.4±1.0o, 1.46±0.0.99 kgf/mm2, 62.0±6.5 N, 38.3±1.6 N, 81.0±11.7 N, 61.0±4.74 N, 45.1±2.4 N, and 76.5±9.8 N respectively. There was significant difference between the physical and gravimetric properties of IT89KD-288, Ife brown, and IT98K-573-1-1 varieties of cowpea.